Pengelolaan Kelas pada Mata Pelajaran PAI Kelas XI MIPA di SMA Negeri 1 Tigo Nagari Kabupaten Pasaman - Adriani, Nova; M, Iswantir; Aprison, Salmiwati Wedra (Al-DYAS, 2023)
The background of this research is that in class management PAI learning at SMA Negeri 1 Tigo Nagari there have been implementing approaches in managing classes, but the application of this class management approach to students has not been able to bring about changes in students' behavior regarding attitudes when studying. In class, for example, there are students who are still noisy when the teacher is explaining the lesson, there are those who go in and out of the class, there are students who talk with their peers during PAI class hours, there are some students who are late for class during PAI class hours. The purpose of this study was to describe classroom management in PAI subjects using the authority approach in class XI MIPA 1 at SMA Negeri 1 Tigo Nagari, Kab. Pasaman and to find out what are the obstacles to class management in class management in PAI subjects using the authority approach in class XI MIPA 1 at SMA Negeri 1 Tigo Nagari, Kab. Passover.This study uses a type of descriptive qualitative research, using Islamic Religious Education (PAI) teacher key informants and supporting informants, namely students. In collecting data, using observation, interviews and documentation. Data analysis using data reduction, data presentation and data verification. To test the validity of the data using source triangulation, namely comparing the results of interviews conducted on key informants and supporting informants with the results of direct observations by the author.The results of this study are summarized as follows: (1) Whereas in class management in the subject of Islamic Religious Education (PAI) in class XI MIPA at SMA Negeri 1 Tigo Nagari Kab. Pasaman, using an authority approach such as an order and prohibition approach, suppression and control, threats and punishment, approach and prohibition, has been carried out well. (2) Class management constraints on PAI subjects in class XI MIPA with an authority approach are: (a) Teachers (b) Students (c) Facilities (d) Time.